Necesidad de incorporar el sindrome de alienación parental en la ley Nº 30364 como modalidad adicional de maltrato psicológico - Esquivel Escobedo, Alessandra Arlet (2018)
This research work entitled "The need for the recognition of parental alienation syndrome as a type of violence and its incorporation in Law 30364". It originates in the need to provide greater protection under Law 30364, to minors who are immersed in conflictive situations. Taking into account that the Parental Alienation Syndrome is not regulated in our country and internationally there are few countries that have legal devices to deal with situations where the syndrome is present; that is why it is necessary that this syndrome is regulated in our country, because family violence is occurring with the passing of time in an unsustainable manner having as main affected the child and the mother, and in this specific case is The child who can suffer from this evil after a conflictive separation from their parents, can generate problems that affect their mental and physical health at a young age. As a result of its treatment at the level of cassations, it was decided to approach this theory oriented to family violence in order to carry out a study on this matter, to determine, among others, what are the arguments used by legal operators, judges, prosecutors and psychologists that support its application or rejection. In this sense the inductive method has been used to verify the hypothesis, the deductive method served to work the arguments contained in the theoretical framework concerning the family, family violence and the Parental Alienation Syndrome. In order to study the codes and other instruments of foreign legislation, the legal hermeneutic method has been applied, as well as an analysis of the judgments of the first instance and the hearing of the Superior Court of Justice of Moquegua, which serves us of base for the present investigation. In addition, interviews were conducted with the legal operators and health professionals in order to let us know their views on the problem addressed; consequently, as already mentioned above, the importance of this research lies in the importance of providing greater protection to the child within the family. Finally, we note that the present investigation will allow us to see if it is necessary to incorporate the Parental Alienation Syndrome as a form of psychological abuse towards the child in the Law N ° 30364 "Law to prevent, eradicate and punish violence against women and children. Members of the family group, "and at the same time serve as a precedent for different investigations in order to overcome what has been achieved so far. The investigation is open.